2PPaRR-2PPaRU: Design, analysis, and optimization of a new 3T1R parallel manipulator with rotational pitch motion. (June 2022) - Zhang, Xiaoshu; Wenxun, Dong; Dai, Li; Chen, Jianneng; Zhao, Xiong
A new 3T1R parallel manipulator (PM) 2PPaRR-2PPaRU with rotational pitch motion is proposed in this paper. In such a mechanism, there are four limbs connected to the moving platform (MP) through several revolute joints and universal joints, and all actuated joints are prismatic joints with an axis along a vertical direction. Mobility and motion characteristics are verified by constraint screw theory. The inverse kinematic solutions and the singularity configurations are derived through kinematic analysis. Next, the workspace analysis and the connection betweenϕ and the volume of the reachable workspace are performed. The local motion/force transmission index is selected to evaluate the local transmission performance of 2PPaRR-2PPaRU PM. Finally, the global motion/force transmission index and the volume of reachable workspace are considered simultaneously to optimize the structural parameters. The 2PPaRR-2PPaRU PM with improved local transmission performance and reachable workspace has been achieved after optimization.